(untitled) (Pregled: časopis za društvena pitanja / Periodical for social issues, 2018)
Review of a book Dayton (Peace) Agreement – Legalization of Genocide in Republic Bosnia and Herzegovina by Academician Prof. Dr. Smail Ĉekić (Sarajevo: Institute for Research of Crimes Against Humanity and International Law of the University of Sarajevo, 2016).